2019
DOI: 10.1017/aae.2019.25
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Adoption of Conservation Agriculture in the Democratic Republic of the Congo

Abstract: Empowering farmers to increase productivity by educating them on conservation agriculture (CA) could contribute to reducing vulnerability, alleviating food insecurity, and fighting poverty while being ecologically sustainable in the Democratic Republic of the Congo. This study assesses the effect of a CA-promotion agriculture program. Findings suggest that location of the farm, training, having accessed credit, belonging to a farmers' group, and being a vulnerable female all drove adoption to varying degrees a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…The literature available on the adoption of technology reveals that the farm size is an important factor that determines the farmers' awareness and their adoption decisions [27][28][29][30]. These studies have shown that large farm sizes increase the ability of farmers to be aware of and to adopt agricultural practices for the potential benefit of their households.…”
Section: Farm Sizementioning
confidence: 99%
“…The literature available on the adoption of technology reveals that the farm size is an important factor that determines the farmers' awareness and their adoption decisions [27][28][29][30]. These studies have shown that large farm sizes increase the ability of farmers to be aware of and to adopt agricultural practices for the potential benefit of their households.…”
Section: Farm Sizementioning
confidence: 99%
“…Households in the nonintervention domain reported walking longer durations to access both their furthest fields and their nearest fallows, which indicates that they were farming geographically farther from their homesteads and extending potentially into the buffer zones and/or PFZs. This presents important social implications beyond deforestation, especially for women, who have important roles in farming and harvesting crops in the DRC and who face increased safety risks when required to travel farther from their homes to cultivate land [48]. A previous study in the same area [28] found that villages that supported higher human populations had generally larger AMZ surface areas; therefore, human population size was likely not the main driver of a village's decision to expand its agricultural activities into the PFZ.…”
Section: Discussionmentioning
confidence: 99%
“…In Angonia, a lack of these inputs is real, forcing farmers to confine CA to a small plot of land. Similarly, Mango et al (2017), Mulimbe et al (2019) and Ntshangase et al (2018) demonstrated how input availability influenced CA outcomes and adoption in South Africa, Lesotho and Malawi. In this regards, the study concludes that the manner in which CA is practiced may lead to dis-adoption at any point because herbicides and appropriate tillage equipment play an important role in the field management.…”
Section: Constraints Hindering Ca Adoption In Angonia Mozambiquementioning
confidence: 92%